UJI AKURASI MESIN PENERJEMAH STATISTIK (MPS) BAHASA INDONESIA KE BAHASA MELAYU SAMBAS DAN MESIN PENERJEMAH STATISTIK (MPS) BAHASA MELAYU SAMBAS KE BAHASA INDONESIA - Hadi, Ibnu (JUSTIN (Jurnal Sistem dan Teknologi Informasi), 2014)
Language  is an  important  means ofcommunication  for humans,  because  language  make  wecan find out the information that we need, at other side wecan  convey  our  ideas. With the rapidly development of technology  in  all sectors,    nowdays the machine translation has been developed to  overcome  languagetranslation  problems. Statistical  machine translation  is  anapproach to  machine translation  with  translation resultsgenerated  on the basis of  statistical  models  whereparameters are  taken  from  the results of  the analysis ofbilingual text corpus (parallel corpus). Parallel corpus is apair of corpus that contain sentences in a language and the translation.  The goal  of this research  is to develop  andimplement of statistical machine translation for translationfrom Indonesian into Sambas Malay and  translation from Sambas Malay into  Indonesian,  and conduct  testing  toobtain  the value of  accuracy  and  quality of  statisticalmachine translation, and also to conduct  testing  to  obtainthe value of  accuracy  and  quality of  statistical  machine translation. In  this study  are  conducted  two  tests,  the firstconducted  tests on  statistical  machine translation of Indonesian  into Sambas Malay translation  and  secondtest on  statistical  machine translation  of Sambas Malay into Indonesian translation. On test  1  (Statistical Machine Translation  of  Indonesian  to  Sambas Malay)  generate  the value of  BLEU  score  of  0.5555  or  55% while    on  Test  2(Statistical  Machine Translation  of Sambas  Malay  toIndonesian) produces BLEU score of 0.4950 or 49%.